CHINA: TRADITIONS, CULTURE AND IDEOLOGY - Shazamanov, Shaazim Ibragimovich (Oriental Journal of Education, 2024)
Social relations between Central Asia and China have developed and today have entered their “golden age”. Swift steps to implement the Shanghai Cooperation Organization project, the One Belt, One Road and the Great Silk Road megaprojects, the development of economic and cultural cooperation, strengthening public diplomacy, cooperation in the field of tourism and sports, as well as the formation of a family despite the existing socio-cultural features act as a new process capable of determining the overall development strategy of the nations of the region. In this regard, analysis of the features of China's development during the reform period, state ideology, political culture and evolution, as well as the study of research by scientists from China and the CIS countries about China is one of the main tasks today. The article uses methods of analysis and synthesis, historicity, systematization, structural and functional analysis.